Minimal Passive Realizations of Generalized Schur Functions in Pontryagin Spaces - Lilleberg, Lassi (Springer, 2020)
Passive discrete-time systems in Pontryagin space setting are investigated. In this case the transfer functions of passive systems, or characteristic functions of contractive operator colligations, are generalized Schur functions. The existence of optimal and *-optimal minimal realizations for generalized Schur functions are proved. By using those realizations, a new definition, which covers the case of generalized Schur functions, is given for defects functions. A criterion due to D.Z. Arov and M.A. Nudelman, when all minimal passive realizations of the same Schur function are unitarily similar, is generalized to the class of generalized Schur functions. The approach used here is new; it relies completely on the theory of passive systems.
Keywords: Operator colligation; Passive system; Transfer function; Defect functions; Generalized Schur class; Contractive operator; Matemaattiset tieteet